2002
DOI: 10.1093/annonc/mdf306
|View full text |Cite
|
Sign up to set email alerts
|

Is first-line single-agent mitoxantrone in the treatment ofhigh-risk metastatic breast cancer patients as effective as combination chemotherapy? No difference in survival but higher quality of life were found in a multicenter randomized trial

Abstract: No significant difference was detected between the treatment with mitoxantrone as a single agent and the combination of low-dose FEC in terms of response or survival; therefore, the imperative of the necessity of first-line combination chemotherapy for patients with high-risk metastatic breast cancer may be questioned. Since toxicity and quality of life score favored the single-agent mitoxantrone treatment arm, this treatment may be offered to patients preferring quality of life to a potential small prolongati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 31 publications
1
14
0
1
Order By: Relevance
“…However, compared with epirubicin alone, use of these combinations did not prolong progression-free interval or OS (17). Comparable results have also been reported in a study in Finland (18) with a similar design and in a study in Germany (19) using single-agent mitoxantrone as the reference regimen. The study in Finland (18) was one of the few studies to clearly compare a sequential single-agent strategy with a combination approach throughout the course of illness.…”
Section: Literature Reviewsupporting
confidence: 72%
“…However, compared with epirubicin alone, use of these combinations did not prolong progression-free interval or OS (17). Comparable results have also been reported in a study in Finland (18) with a similar design and in a study in Germany (19) using single-agent mitoxantrone as the reference regimen. The study in Finland (18) was one of the few studies to clearly compare a sequential single-agent strategy with a combination approach throughout the course of illness.…”
Section: Literature Reviewsupporting
confidence: 72%
“…In 12 trials (4041 patients, 37%) [12,14,15,18,22,24,27,29,[35][36][37][39][40][41] the authors used QoL findings in the abstract as a part of their decision- making process for choosing the best treatment option. Three of these 12 studies considered QoL as a primary endpoint [14,15,35,36].…”
Section: Qol Resultsmentioning
confidence: 99%
“…Three of these 12 studies considered QoL as a primary endpoint [14,15,35,36]. Eight trials (2828 patients, 26%) [12,14,15,22,24,26,27,29,36,40] reported significantly (p<0.05) more favourable outcomes in terms of QoL (five compared different drugs, three compared different schedules) and in seven it was also possible to identify the specific QoL dimension involved (one only physical dimension [24], two only psychological dimension [26,36], four both [12,14,15,27,29]). Two of the eight studies considered QoL as a primary outcome measure [14,15,36].…”
Section: Qol Resultsmentioning
confidence: 99%
“…Les toxicité s de grades 3 et 4 é taient, dans pratiquement tous les cas, plus fré quentes pour les associations. Par contre, seulement deux é tudes montraient une diffé rence significative entre les deux bras pour les scores de QdV pour certains paramè tres (é tude FEC versus mitoxantrone) [33] ou à certains temps de mesure (é tude gemcitabine plus paclitaxel versus paclitaxel) [45]. Dans l'interpré -tation clinique des ré sultats de QdV obtenus dans cette derniè re é tude, Hopwood et al observaient que l'amé lioration de la QdV é tait significativement associé e à la ré ponse tumorale et au nombre de cycles complé té s tandis qu'une alté ration de la QdV é tait plutô t associé e à la dé té rioration du fonctionnement et de l'é tat psychologique plutô t qu'à la toxicité du traitement [36].…”
Section: Vers Un Meilleur Choix Thé Rapeutiqueunclassified